A maturing market : the Iberian book world in the first half of the seventeenth century - Wilkinson, Alexander S., 1975-; Ulla Lorenzo, Alejandra (Brill, 2017)
Within just a generation or two of its arrival, print had become a ubiquitous and spirited part of Spain and Portugal's urban cultures. It serviced an ever-expanding reading public, as well as many and varied practical quotidian needs. Its impact on society was multi-dimensional and complex, and its social reach far broader than the civic or ecclesiastical elites were ever to be entirely comfortable with. This cross-disciplinary volume of essays focuses on the maturing marketplace for print in the first half of the seventeenth century, shedding new light on some important transformations, with authors and publishers seizing opportunities available to them - negotiating the regulatory efforts of the censors, and scrambling to reconfigure their relationship with their readers.
Keywords: Book industries and trade -- Spain -- History -- 17th century.; Book industries and trade -- Portugal -- History -- 17th century.; Books and reading -- Spain -- History -- 17th century.; Books and reading -- Portugal -- History -- 17th century.; Publishers and publishing -- Spain -- History -- 17th century.; Publishers and publishing -- Portugal -- History -- 17th century.; Authors and publishers -- Spain -- History -- 17th century.; Authors and publishers -- Portugal -- History -- 17th century.; Livres -- Industrie -- Espagne -- Histoire -- 17e siècle.; Livres -- Industrie -- Portugal -- Histoire -- 17e siècle.; Livres et lecture -- Espagne -- Histoire -- 17e siècle.; Livres et lecture -- Portugal -- Histoire -- 17e siècle.; Écrivains et éditeurs -- Espagne -- Histoire -- 17e siècle.; Écrivains et éditeurs -- Portugal -- Histoire -- 17e siècle.; BUSINESS & ECONOMICS -- Commerce.; BUSINESS & ECONOMICS -- Marketing -- General.; BUSINESS & ECONOMICS -- Sales & Selling -- General.; Authors and publishers; Book industries and trade; Books and reading; Publishers and publishing; Portugal; Spain; 1600-1699; History